Herbal medicines in the treatment of tinnitus: An updated review - Liu, Dongliang; Hu, Yue; Wang, Dali; Han, Hezhou; Wang, Yi; Wang, Xilu; Zhou, Zhaoyu; Ma, Xiulan; Dong, Yaodong (Frontiers in Pharmacology, 2023)
Tinnitus is perception of sound in the absence of an apparent external acoustic stimulus. The condition is prevalent in adults, especially the elderly (≥65 years), and may be associated with cognitive function decline and significantly impacts on the quality of life, heralding difficulties in managing this challenging disorder. Interventions for tinnitus have been varied. However, drugs have not yet been approved for the treatment of tinnitus and there is no pharmacotherapy recommended by existing guidelines. Still, herbal medicines are used for the treatment of tinnitus in many countries, especially Gingko (G.) biloba. In the current updated literature review, we evaluated the efficacy of herbal medicines in the treatment of tinnitus by reviewing the evidence of relevant randomized controlled trials. The authors also highlight some of the issues in clinical trials of herbal medicines given that currently available evidence on herbal medicines for tinnitus is overall of insufficient quality and the conclusions from existing trials are conflicting. Nevertheless, there is a clear and urgent need for safe and effective pharmacotherapy of tinnitus.